The Development of Guidance and Counseling Services in 4.0 Era: Lesbian Behavior - Fira Ramli; Riska Ahmad; Yarmis Syukur (Jurnal Aplikasi IPTEK Indonesia, 2019)
Lesbian behavior affects adolescents. It happens because, physically, adolescent have experienced growth of maturity in sexual function that is why the sexual drive is getting stronger. Several factors that influence the tendency of lesbians mostly happen in early adulthood. This research was development research with the ADDIE model. The total participants of this study were 183 junior high school students chosen by using purposive sampling. In the analysis phase, the researchers identified the tendency of adolescents to behave in lesbians in some ways, such as used self-identification instruments, determined e-module material (design), developed instruments to determine eligibility by experts and the use of e-modules by counselors (development), conducted limited trials to 30 students in the school (implementation), and assessed the overall aspects of product usage by the counselor at school (evaluation). Based on the development of this e-module, it can be concluded that the product was workable in content and appearance because it has been empirically tested and ready to be used for adolescent in school.